User-Generated content and its impact on journalism - Bueno Olivera, Esther (2020)
The following article explores users’ interaction with the media and how technological tools have allowed users to easily generate information in great volumes for the media, known as User-Generated Content (UGC). Mobile devices have undoubtedly become a powerful tool to report to the media through messages, pictures and videos. However, there are some users who deliberately create false information, known as “fake news”, which rapidly spreads through social networks. Quite often, journalists pick up this information and their job is to verify its veracity before publishing.